Chemical composition and antibacterial activities of Rhus tripartita essential oils from Algeria - Khaoula Benlembarek; Takia Lograda; Messaoud Ramdani; Gilles figueredo; Pierre Chalard (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Benlembarek K, Lograda T, Ramdani M, Figueredo G, Chalard P. 2021. Chemical composition and antibacterial activities of Rhus tripartita essential oils from Algeria. Biodiversitas 22: 482-492. The yield of Rhus tripartita essential oils in Algeria is low with an average of 0.16 ± 0.017. The chemical composition of the oils was determined by GC-GC / MS analysis. Seventy-eight compounds were identified with an average of 92.3 ± 26.4% in the total oil. The ?-pinene (58.72 ± 14.45%), ?3-carene (5.21 ± 6.89%), caryophyllene-Z (4.55 ± 4.68%) and ?-pinene (3.07 ± 1 85%) are the major components of the oils of R. tripartita populations. The results reveal a notable difference between the chemical composition of essential oils from male and female populations. The oils of this species are composed of four chemotypes, the ?3-carene, ?-pinene; limonene chemotype characterizes the male populations of Tamanrasset and Boussaada. The ?-pinene - ?3-carene - caryophyllene-Z chemotype characterizes the male populations of M’sila and Mergueb. The female M’sila population is characterized by the ?-pinene - ?3-carene - ?-cadinene chemotype. The remaining populations show the ?-pinene - ?-pinene - caryophyllene-Z chemotype. The evaluation of antibacterial activities reveals that Staphylococcus aureus, Escherichia coli, Proteus mirabilis and Pseudomonas aeruginosa are not sensitive to the essential oils of R. tripartita. In contrast, Enterococcus faecalis is the most sensitive to the oils.